Race, Class, and Gender Inequality in Sports: A Socio-Historical Analysis - Dipak Ghosh (Penerbit Hellow Pustaka, 2026)
Although sports are commonly portrayed as symbols of physical ability, competition, and equality, in reality, they are deeply influenced by the prevailing structures of race, class, and gender in society. Historically, sports have never existed as a sphere separate from social realities; rather, they have sometimes reflected and at other times reproduced social inequalities. An analysis of the development of sports in India, and particularly Bengal, reveals that participation, opportunities, recognition, and representation in sports have never been distributed equally. This research paper presents a socio-historical analysis of race, class, and gender inequality in sports. It examines how colonial and contemporary sports institutions, educational systems, and state policies have enabled certain social groups to dominate sports arenas. The predominance of upper-caste and middle-class groups has historically limited the participation of lower-caste, Dalit, and indigenous communities. Similarly, class-based disparities in economic resources, leisure time, and training opportunities have unevenly shaped access to sports. Gender inequality forms a central focus of this paper. Historically, sports have been constructed as a male-dominated domain, which has exposed women athletes to social conservatism, notions of modesty, and institutional neglect. Women athletes have often been assessed more on their bodies, attire, and personal lives rather than their skills, further reinforcing gender-based inequality. The main argument of this research is that race, class, and gender inequalities in sports are not isolated problems; they are interconnected and embedded within broader social power structures. At the same time, sports have the potential to challenge these inequalities. Through inclusive policies and social awareness, sports can serve as a vital medium for social justice and equality.